Rapid detection of Alternaria spp. by PCR in the newly created forest plantations on the drained bottom of the Aral Sea - A. Sherimbetov; S. Sherimbetov; B. Adilov; D. Ruzmetov; J. Shavkiev (Regulatory Mechanisms in Biosystems, 2024)
Salinization and drought are the most important abiotic stress factors causing significant impact to the agriculture of Uzbekistan. To eliminate the negative consequences of the drying of the Aral Sea, large-scale works are currently being conducted on this territory to create protective forest plantations of halophytic trees and shrubs. An important issue in the protection of forest plantations is the isolation, identification and monitoring of phytopathogenic fungi associated with these forest plantations. The study's objective was to isolate Alternaria fungi from Haloxylon aphyllum (Minkw.) Iljin, Tamarix hispida Willd., T. ramossisima Ledeb. and to also apply a diagnostic marker using PCR assays to detect and identify Alternaria pathogens in these plants. As a result of the study, 10 strains of Alternaria fungi were isolated from plant samples of black saxaul – Haloxylon aphyllum, and two tamarisk species – Tamarix hispida, Tamarix ramossisima. The dominant species was: Alternaria tenuissima (Kunze) Wiltshire. β-tubulin gene was used as a molecular marker to distinguish and identify Alternaria spp in 34 leaf samples of Haloxylon aphyllum, Tamarix hispida and Tamarix ramossisima. The primer set used in the PCR assay was shown to be capable of detecting the presence of Alternaria in the leaves. Therefore, a β-tubulin-based diagnostic marker can be widely applied for monitoring of Alternaria infecting a wide-range of halophytic trees and shrubs in the protective forest plantations.